The Reward of Loyalty and Ruth's Example for Believers - Simon Stefanus; Djone Georges Nicolas (East Asian Journal of Multidisciplinary Research, 2022)
Loyalty is always interesting because it is an essential part of human life, including spiritual life. However, finding faithful people is not easy since the creation of man until now, including in the lives of those who believe in Jesus Christ. This study analyzes loyalty's rewards and Ruth's example for believers. The approach in this research is descriptive and hermeneutic qualitative methods, and data collection through various sources such as the Bible, journals, and books. The result: First, God made Ruth liked and respected by humans. Second, Ruth is recorded as an example of faith in the Bible. In conclusion, believers in the journey of their lives must remain faithful to God as evidence of faith in Him because the faithfulness of believers is not in vain. Behind their faithfulness, there is an unexpected reward from God.